Local Labour Market Conditions on Immigrants' Arrival and Children's School Performance - Marianne Roed; Pal Schone; Janis Umblijs (Institute of Labor Economics (IZA), 2018)
In this paper we analyse the impact of labour market conditions at immigration on school performance for the immigrants' children. First, we establish the direct effect of initial labour market conditions on later labour market performance for the father. Along with several other studies in this field we find that later labour market performance of the father (measured by labour earnings and accumulated work experience) depend significantly initial labour market conditions. Second, we find evidence that this initial effect feeds into the children's school performance. Concretely, for the sons, we find a positive impact of initial favourable labour market conditions of the father on the grade point average in lower secondary school. Daughters' school performance seems to be unrelated to the same initial labour market conditions.
Keywords: I20; J18; J61; 330; educational outcomes; immigration; local labour market conditions